2004
DOI: 10.3354/dao058215
|View full text |Cite
|
Sign up to set email alerts
|

Excretory calcinosis: a new fatal disease of wild American lobsters Homarus americanus

Abstract: A significant number of moribund and dead lobsters Homarus americanus were reported to New York state authorities by lobster fishers in Long Island Sound (LIS) during the summer of 2002. Morbid lobsters were characterised by an orange discolouration of the abdomen, lethargy, an excess of epibionts and poor post-capture survival. On necropsy, severe extensive multifocal or diffuse mineralised granulomatous inflammation of the gills and antennal glands was the most striking pathology. In the gills, granulomas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In 2002, similar gill pathologies were observed for moribund and dead lobsters from Long Island Sound (Dove et al 2004). Although these lobsters were not reported specifically to have shell disease, granulomas were frequently seen to be embolisedin the gill filaments, resulting in congestion, ischemia, and coagulative necrosis of gill tissues.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In 2002, similar gill pathologies were observed for moribund and dead lobsters from Long Island Sound (Dove et al 2004). Although these lobsters were not reported specifically to have shell disease, granulomas were frequently seen to be embolisedin the gill filaments, resulting in congestion, ischemia, and coagulative necrosis of gill tissues.…”
Section: Discussionmentioning
confidence: 63%
“…Although these lobsters were not reported specifically to have shell disease, granulomas were frequently seen to be embolisedin the gill filaments, resulting in congestion, ischemia, and coagulative necrosis of gill tissues. Dove et al (2004) hypothesised that the lobster deaths were a result of hypercapnia (excess CO 2 in the haemolymph) caused by high sea temperatures (c. 23°C) observed that year. They explained that temperature-related respiratory stress could cause disruptions of the calcium chemistry of lobsters in favour of deposition of calcium minerals in soft tissues and, under appropriate conditions, could represent a fatal positive feedback loop, i.e., cause death (Dove et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 Bowser and Rosemark observed globular, calcium-containing mineral deposits on and in the inner surface of the shed exoskeletons of many juvenile lobsters (H. americanus and H. americanus  H. gammarus hybrids) during an artificial diet trial. 4 The lobsters died during or shortly after molting with dietary stress considered a contributing factor.…”
mentioning
confidence: 99%
“…Dove et al described ''excretory calcinosis'' as a condition of extracellular calcium carbonate deposits affecting a significant number of lobsters in 2002. 7 The condition involved the antennal glands and gills, which showed marked inflammation and occasionally necrosis in more chronic lesions. 7 Increased bottom water temperature was suggested as a possible cause.…”
mentioning
confidence: 99%